ULTRASOUND MONITORING OF CONSOLIDATION PROCESSES IN FRACTURES OF LONG TUBULAR BONES IN OSTEOSYNTHESIS USING BIOACTIVE IMPLANTS - V. D. Zavadovskaya; V. P. Popov; O. E. Akbasheva; E. G. Grigor’ev; T. V. Druzhinina (Вестник рентгенологии и радиологии, 2016)
Objective: to show the capabilities of ultrasound monitoring to assess consolidation processes in fractures of long tubular bones in the use of bioactive material-containing implants.Material and methods. Eighty-two (45.1%) patients whose bone fragments had been fixed with bioactive material-coated plates and 100 (54.9%) patients with bioinert material-coated ones were examined. Consolidation changes were estimated by ultrasound and X-ray studies 2, 4, 6, and 12 months after surgery. Bone metabolic changes were determined by US osteometry 2 months following surgery. Ultrasound data were compared with the biochemical markers: C-terminal telopeptide (CrossLaps) and osteocalcin.Results and conclusions. Ultrasound monitoring of the rates of consolidation and the time course of changes in bone strength versus the biochemical markers established the positive effect of bioactive plates on the process of consolidation in fractures of tubular bones and made it possible to consider local osteopenic syndrome to be a prognostically favorable sign of timely callus formation.